2011
DOI: 10.1158/0008-5472.can-10-4261
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting Tumor Hypoxia: Suppression of Breast Tumor Growth and Metastasis by Novel Carbonic Anhydrase IX Inhibitors

Abstract: Carbonic anhydrase IX (CAIX) is a hypoxia and HIF-1-inducible protein that regulates intra-and extracellular pH under hypoxic conditions and promotes tumor cell survival and invasion in hypoxic microenvironments. Interrogation of 3,630 human breast cancers provided definitive evidence of CAIX as an independent poor prognostic biomarker for distant metastases and survival. shRNA-mediated depletion of CAIX expression in 4T1 mouse metastatic breast cancer cells capable of inducing CAIX in hypoxia resulted in regr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
646
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 671 publications
(687 citation statements)
references
References 44 publications
32
646
0
1
Order By: Relevance
“…Furthermore, some of these compounds show significant primary tumor growth inhibitory effects in a mouse breast cancer model. Correlated with the previous demonstration 15 of their antimetastatic effects, we claim that members of this class of compounds possess important anticancer activity through a novel mechanism of action that takes advantage of the fact that CA IX and XII are overexpressed only in hypoxic tumors (which do not respond to classical chemo-and radiotherapy) and exhibit very limited expression in normal tissues. Thus, tumor CA IX/ XII inhibition may lead to significantly fewer side effects compared to classical anticancer agents in clinical use.…”
Section: ■ Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…Furthermore, some of these compounds show significant primary tumor growth inhibitory effects in a mouse breast cancer model. Correlated with the previous demonstration 15 of their antimetastatic effects, we claim that members of this class of compounds possess important anticancer activity through a novel mechanism of action that takes advantage of the fact that CA IX and XII are overexpressed only in hypoxic tumors (which do not respond to classical chemo-and radiotherapy) and exhibit very limited expression in normal tissues. Thus, tumor CA IX/ XII inhibition may lead to significantly fewer side effects compared to classical anticancer agents in clinical use.…”
Section: ■ Introductionsupporting
confidence: 62%
“…15 Furthermore, we have demonstrated that treatment of 4T1 tumors with certain novel ureido-substituted benzenesulfonamides 14 results in attenuation of primary tumor growth and metastasis in spontaneous 15 and experimental metastatic disease. 14,15 Novel CA IX-selective glycosyl coumarin inhibitors were also found to limit the metastatic burden in a model of experimental metastasis. 15 To evaluate the effect of pharmacologic inhibition of CA IX activity on primary tumor growth in vivo using the novel glycosyl coumarin compounds described here, we treated mice harboring established 4T1 tumors with the glycosyl coumarin 6, a compound that demonstrates excellent CA IX and XII inhibitory activities in vitro, and a very good selectivity ratio for inhibiting the tumor-associated CA isoforms compared to the cytosolic CA isoforms, as discussed above.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although some recently published small molecule inhibitors (27,28) successfully target the enzymatic activity of CAIX, the work described here uses a different therapeutic approach in exploiting CAIX as an anchor for the selective delivery of a toxic payload to tumors via an antibody-based therapeutic. A rigorous discovery cascade was implemented to generate and select fully human antibodies that are highly selective for binding to, and internalization by, CAIX-expressing cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%